Avaliação de uma metodologia para projeto de pequenas barragens de terra no semiárido: construção, ensaios e modelagem numérica - Leme, Rosiel Ferreira (2015)
A common problem of the Brazilian semiarid regions is water scarcity. An alternative to attenuate this severe regional problem consists in storing water during the rainy season, in dams with small storage volumes, usually built with inefficiently compacted embankments, which can contribute to the collapse during the first filling. The main goal of this work is to evaluate a construction methodology for earth dams in semiarid regions, taking into account the problems of inadequate compaction and water shortages. To achieve this, a study was done on a theoretical and experimental basis, in order to better understand the mechanical behavior of small dams that collapse during the first filling. An experimental dam was built in Quixadá-CE, following the proposition of Miranda (1988), which suggests a zoned cross section, built with low water content, with a better compacted core and side slopes with less efficient compaction. The embankment of this experimental dam was instrumented with piezometers (standpipes) and limnimetric rules, to monitor the filling and operation stages. Another developed study in this research refers to the avant-garde evaluation of suction in earth dams, using a device developed by researchers from the Department of Agricultural Engineering, at the Federal University of Ceará, a capacitive sensor. To obtain the geotechnical parameters for the embankment soil, some laboratory tests were performed, such as characterization tests, compaction, consolidation and permeability tests, as well as shear strength and triaxial compression (saturated and unsaturated) ones, and also tests to determine the soil-water characteristic curve (using the filter paper method). The results were used in a numerical modeling of transient flow, using the software Slide, associated with UNSTRUCT, to predict the stress-strain behavior of the experimental dam. The results pointed to the occurrence of collapse in the soil structure of the slopes, which indeed happened after the first filling, since large longitudinal cracks were found in loco. The dam stability was also evaluated, by reducing the shear strength parameters, noting its stability, and thus proving efficient what Miranda (1988) proposed: a zoned embankment built with reduced costs of earthworks and low water consumption, contributing to the development of a low-cost methodology for the construction of small dams in the Brazilian semiarid.